HUBUNGAN ANTARA NAFSU MAKAN DENGAN TINGKAT STRES PADA PASIEN KANKER PAYUDARA YANG MENJALANI KEMOTERAPI DI RUMAH SAKIT MURNI TEGUH - Yasinta Yolan Selviani Gulo; Muhammad Taufik Daniel Hasibuan; Lenny Lusia Simatupang (JOURNAL SAINS STUDENT RESEARCH, 2026)
Background: The action that is often done in the management of breast cancer patients is Chemotherapy. Chemotherapy has an impact on appetite and stress levels of cancer patients. Disruption of physical and psychological conditions will worsen the health condition of breast cancer patients. Objective: To identify the relationship between appetite and stress levels in breast cancer patients undergoing chemotherapy at Murni Teguh Hospital. Method: The type of research used is quantitative with a research design using a cross-sectional design. The population in this study were 98 breast cancer patients undergoing chemotherapy at Murni Teguh Hospital and the number of samples was 32 respondents. In the appetite variable, primary data was collected using the SNAQ (Simplified Nutritional Appetite Questionnaire) questionnaire and for measuring stress levels in this study using the Perceived Stress Scale (PSS). The statistical test used was the Spearman Rho correlation test. Results: There is a significant relationship between appetite and stress levels in breast cancer patients undergoing chemotherapy at Murni Teguh Hospital with a correlation coefficient of -0.497 indicating a moderate negative relationship between the two variables. The significance value (p-value) is 0.004 (p <0.05). Conclusion: There is a relationship between appetite and stress levels in breast cancer patients undergoing chemotherapy at Murni Teguh Hospital. This indicates that psychological aspects in the form of stress have an important role in influencing the physiological condition of patients, especially appetite, during chemotherapy treatment.